"I missed open arms": The need for connectedness among Black youth affected by parental drug use. (July 2020) - Offiong, Asari; Powell, Terrinieka W.; Lewis, Quiana; Smith, Bianca; Prioleau, Morgan
Highlights: Parental drug use leads youth to miss opportunities for healthy development. Extended family are integral to meeting youth's physical and emotional needs. Youth desire long term connections to committed and consistent adults. Missed connections lead to early engagement in risky behaviors. Abstract: Parental drug use has significant impacts on the physical, behavioral and social well-being of adolescents, particularly those from disenfranchised communities. We conducted a qualitative study to understand connectedness among Black youth affected by parental drug use in Baltimore, Maryland USA. In-depth interviews (N = 30) were conducted with three groups: parents with a history of drug use, youth (18-24yo) who had a biological parent with a history of drug use and youth providers with experience working with families affected by drug use. Data were analyzed inductively using a content analytic approach. Three salient themes emerged: (1) missing parental connections, (2) the desire for consistent, trusted adults and (3) the consequences of missed connections. All participants emphasized the limited emotional support and guidance provided to youth affected by parental drug use. However, extended family members (e.g., grandmothers, aunts, and older siblings) and community mentors stepped in to fulfill unmet needs, when possible. The consequences of missed connections were increased involvement in risky behaviors, fewer basic necessities and a missed childhood. Findings from the study deepen the understanding of how to support the well-being of youth impacted by parental drug use and highlight the value of including the voices of vulnerable families in research.